Analisis Yuridis Penyelenggaraan Kampanye Di Lingkungan Universitas - Aprianto, Sandi; royani, ferawati; Suaka, Mardhatilla (Lex Librum : Jurnal Ilmu Hukum, 2024)
General elections are a constitutional process of changing power. In one of the stages that always occurs in general elections, there is the campaign stage which is the momentum for general election participants to introduce themselves. Campaigning is an integral part of elections, but not all public spaces can be used as campaign venues, including educational institutions. Historically, in Indonesia, the ban on campaigning in educational environments was implemented in the 2004, 2009 and 2014 elections, and most recently in the 2019 elections through Law Number 7 of 2017 concerning Elections. Along the way, there was Constitutional Court Decision Number 65/PUU-XXI/2023 which basically allowed general election participants to campaign in educational facilities or university environments. Based on this, the author will raise the problem, namely how to investigate the mathematics of campaign implementation within a university environment, then what is the juridical analysis of views and follow-up to Constitutional Court Decision No. 65/PUU- XXI/2023 for the implementation of the Election Campaign inSchool. The writing method used is normative juridical. In the end, the author sees that in essence the problem in the Constitutional Court Decision Number 65/PUU-XXI/2023 is more a matter of norms. According to the author, the follow-up to the Constitutional Court Decision Number 65/PUU-XXI/2023 is quite difficult and the General Election Commission needs to carefully regulate it in technical regulations.